Covenanting Exchanges with the French Court during the Wars for the Three Kingdoms - Allan I. MACINNES (E-REA)
In 1638, Scots opposed to the imposition of administrative, social, economic and religious uniformity by Charles I exercised their right of resistance by issuing a patriotic manifesto, the National Covenant, which sought to impose permanent checks on monarchy. This resistance was carried further by the Scottish Covenanters fighting and winning the Bishops’ Wars in 1639-40 and then exporting their revolution through armed intervention in Ireland from 1642 and in England from 1644. The Scottish Covenanters’ alliance with the English Parliamentarians was formalised by the Solemn League and Covenant which again sought to impose permanent checks on monarchy throughout the three Stuart kingdoms. But these events cannot be viewed solely as British and Irish Civil Wars. They must be contextualised in relation to the Thirty Years War and particularly to the determination of France under both Cardinals Richelieu and Mazarin to supplant the Spanish and Austrian Habsburgs as the foremost European power. While much work has recently been done on the diplomatic links of the principal protagonists in the Civil Wars, the importance of France to Scottish Covenanters, English Parliamentarians and Irish Confederates in their tangled and tortuous relationships among themselves and with Charles I remains relatively underworked. This article does not attempt a comprehensive review, but sketches out the intricacies of Covenanting exchanges with the French Court before all prospects of a revived ‘auld alliance’ were crushed by the occupation of Scotland by Oliver Cromwell and his English regicides in 1651.